Autism in the Workplace: An Investigation of Germany and the United States - Bauer, Melanie; Doubleday, Garrett; Erffmeyer, Johannah; Hanson-Rasmussen, Nancy; Lentz, Paula J. (My University, 2017)
The research team examined the perceptions on whether initiatives in training and hiring individuals with autism can be a competitive advantage. The investigators conducted in-person interviews and explored the initiatives and the perceptions of employees and employers of a variety of companies in both the US and Germany to gain an understanding the potential of individuals with Autism Spectrum Disorder (ASD) as successful members in the workforce and an understanding of the German model of preparing individuals with ASD. The team traveled to Germany because it is the leader in vocational programs for people with ASD.
Color poster with text, charts, and graphs
Keywords: Autism spectrum disorders; Vocational guidance; Workplace; Posters